The effect of the Rossby number on vortex shedding and associated surface pressure drag in low Froude number flows - Gutiérrez Camacho, Jorge A. (1998)
The effect of the Robbby number in the shedding of vortices and the associated surface pressure drag is investigated. Four different case studies are analysed, namely Ro=∞, Ro=0.2, Ro=0.4 and Ro=0.8. The flows investigated here are simulated by means of a three-dimensional numerical, non-hydrostatic, non-linear numerical model. It is found that the shedding frequency increases with increasing Rossby number in the experiments wich include background rotation. It is also found that vortex shedding leaves a trace in the surface pressure drag.